Efektivitas Pidana Pengawasan dan Pidana Kerja Sosial dalam Mengurangi Overcrowding Lapas - Andree Washington Hasiholan; Lonna Yohanes Lengkong; Tomson Situmeang (Pusat Kajian Lembaga Pemasyarakatan, Fakultas Hukum, Universitas Kristen Indonesia, 2026)
This study aims to analyze the juridical effectiveness of supervised sentencing and community service as alternative punishment instruments introduced by the National Criminal Code under Law Number 1 of 2023 to address the chronic problem of prison overcrowding in Indonesia. This research employs a normative legal research method using two simultaneous approaches, namely the statute approach and the conceptual approach. Legal materials were collected through documentary study of legislation, legal doctrine, jurisprudence, and national and international legal literature, then analyzed qualitatively using the deductive syllogism method. The results indicate that supervised sentencing, applicable to convicts facing imprisonment of no more than two years, relocates the rehabilitation process from total institutions to a controlled social environment under the supervision of the Correctional Guidance Center. Meanwhile, community service with a duration of 24 to 240 hours effectively substitutes short-term imprisonment for offenses carrying penalties of less than five years. If implemented optimally, both instruments are projected to reduce the prison population by 20 to 30 percent within the first five years. Comparative analysis with non-custodial sanction systems in the Netherlands, England, Wales, and Australia confirms their effectiveness. This study concludes that the successful implementation of both instruments depends critically on four main pillars: the availability of comprehensive technical regulations, adequate institutional capacity of the Correctional Guidance Center, judicial commitment to consistently applying non-custodial options, and public acceptance of restorative justice philosophy.